Coupled Axial and Lateral Displacement Estimation for Elasticity Imaging (2010)
The determination of axial and lateral displacement in a material subject to compression is determined by fitting a multi-dimensional model function to the match between corresponding portions of the material in two states of compression. In one embodiment, iso-contour lines in a correlation between a reference kernel and a target kernel are fit to an ellipse whose center defines the maximum correlation and hence the displacement.